Optimasi Pengendalian Persediaan dengan Metode Reorder Point dalam Pengembangan Aplikasi Kontrol Stok Berbasis Web - Maulidi, Rakhmad; Listianti, Prima (Politeknik Negeri Batam, 2023)
Stock control is a process of keeping track of owned items, their location, and their movements in and out of storage. It helps businesses to manage their inventory efficiently and meet consumer demand while reducing the cost of storing goods. However, online shops like Omah Mode often struggle to meet the demand of consumers due to the lack of a stock control system, resulting in penalties from the marketplace. To solve this problem, a web-based stock control application was designed using the reorder point method. This method determines the minimum stock of goods that should be in the warehouse and the right time to order goods with low stock from suppliers. The purpose of this research is to develop an inventory control system that displays the minimum stock of goods needed in the warehouse. The study used the SDLC Prototype method, consisting of needs analysis, prototype making, prototype evaluation, system coding, system testing, system evaluation, and system use. The results showed that the system created has an 85.71% accuracy rate based on a comparison of manual calculations and system calculations of 28 sample items.